KEPUTUSAN PEMBELIAN E-COMMERCE: PERAN PERCEIVED EASE OF USE, PERCEIVED USEFULNESS DAN ONLINE SHOPPING EXPERIENCE - Laras Fitri Aini Hasibuan; Saidun Hutasuhut (Smart Education, 2026)
Abstract: This study aims to analyze the effect of Perceived Ease of Use, Perceived Usefulness, and Online Shopping Experience on Purchase Decisions in the Lazada application among students of the Faculty of Economics, Universitas Negeri Medan. This research employs a quantitative approach with multiple linear regression analysis. The sample consisted of 128 respondents selected through purposive sampling technique. The results show that Perceived Ease of Use has a positive and significant effect on Purchase Decisions (t = 6.278, sig. = 0.000), while Perceived Usefulness does not significantly affect Purchase Decisions (t = 0.359, sig. = 0.720). Online Shopping Experience has a positive and significant effect on Purchase Decisions (t = 2.154, sig. = 0.033). Simultaneously, all three variables significantly influence Purchase Decisions (F = 84.010, sig. = 0.000) with a coefficient of determination of 66.2%. These findings indicate that ease of application use and quality of online shopping experience are the primary factors driving purchase decisions among students on the Lazada platform. Keywords: purchase decision; perceived ease of use; perceived usefulness; online shopping experience; e-commerce. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh Perceived Ease of Use, Perceived Usefulness, dan Online Shopping Experience terhadap Keputusan Pembelian di aplikasi Lazada pada mahasiswa Fakultas Ekonomi Universitas Negeri Medan. Penelitian menggunakan pendekatan kuantitatif dengan analisis regresi linier berganda. Sampel berjumlah 128 responden yang dipilih melalui teknik purposive sampling. Hasil penelitian menunjukkan bahwa Perceived Ease of Use berpengaruh positif dan signifikan terhadap Keputusan Pembelian (t = 6,278; sig. = 0,000), sedangkan Perceived Usefulness tidak berpengaruh signifikan (t = 0,359; sig. = 0,720). Online Shopping Experience berpengaruh positif dan signifikan terhadap Keputusan Pembelian (t = 2,154; sig. = 0,033). Secara simultan, ketiga variabel berpengaruh signifikan terhadap Keputusan Pembelian (F = 84,010; sig. = 0,000) dengan koefisien determinasi sebesar 66,2%. Temuan ini menunjukkan bahwa kemudahan penggunaan aplikasi dan kualitas pengalaman belanja online merupakan faktor utama yang mendorong keputusan pembelian mahasiswa pada platform Lazada. Kata kunci: keputusan pembelian; perceived ease of use; perceived usefulness; online shopping experience; e-commerce.